Respostas

2014-05-21T19:21:15-03:00
5x(x+1)+(x-4)²=16+2x                                                                                                                       5x+5+5x+x-16=16+2x                                                                                                                           10x+1x-2x=+16+16-5                                                                                                                           11x-2x=    32-5                                                                                                                                     9x=27                                                                                                                                               x=27/9                  3